Multiplexing and operational scenarios - Shah, Asadullah; Abdullah Zammarh, Nuha (IIUM Press, 2011)
The design of multiplexer operation can be based upon certain simulation parameters. In this chapter a design of STDM is based upon some parameters considering a 64 Kbps satellite channel. Allowing each user a capacity of 6.4kbps, 10 users can be multiplexed in a normal situation. Using VAD and packet discarding for each of the users allmv more users on the same link. In this chapter design architecture is proposed and explained in detail.